AI-Driven Incident Management in Retail : A Case Study - Manpreet Singh Sachdeva (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the strategic implementation of artificial intelligence to transform incident management processes and enhance operational efficiency in e-commerce operations. In response to challenges including cart abandonment, system downtimes, slow incident response, and inconsistent customer support, the organization developed a comprehensive AI-driven approach encompassing advanced monitoring, predictive maintenance, and automated incident resolution. The implementation revolutionized the technical infrastructure through machine learning algorithms, natural language processing, and advanced analytics, significantly improving system reliability, customer satisfaction, and operational efficiency. This transformation addressed immediate operational challenges and established new benchmarks for the retail industry, demonstrating the transformative potential of AI in modern e-commerce operations while providing valuable insights for organizations seeking to enhance their incident management capabilities through technological innovation.